A quest for soft power: Turkey and the Syrian refugee crisis. Issue 4 (6th November 2017) - Cevik, Senem; Sevin, Efe
Abstract : Purpose: The purpose of this paper is to bring a communication management perspective to how nations might use their involvement in humanitarian responses to refugee crisis in attempts to improve their global standing through a case study of Turkish efforts during the Syrian Civil War. Design/methodology/approach: In order to assess the context of Turkey's attempts to communicate its humanitarian response to the Syrian refugee crisis and its political discourse, the authors use a two-level analysis. The authors utilize a framing analysis and the informational framework of public diplomacy. The authors conduct a framing analysis of 14 speeches delivered by President Recep Tayyip Erdogan and Foreign Minister Mevlüt Çavusoglu at various international platforms in order to determine the frames and the information frame strategies employed. The authors investigate how Turkey managed its communication efforts and the ways in which the frames are used to reflect Turkey's nation brand. Findings: The analysis indicates that Turkey uses three frames: benevolent country, righteous side, and global power. These frames indicate that Turkey sees the refugee crisis as a problem resulting from the inefficiency of the international community and presents the "Turkish model" as the benevolent and righteous example to overcome these inefficiencies. Based on the information framework strategies used, it can be argued that the positive impact of these frames on the Turkish brand will be limited to certain audiences mainly due to the communication priorities of the country. Originality/value: This study provides a novel communication management outlook on humanitarian aid and public diplomacy through an analysis of Turkey as an illustrative case exemplifying communication of development. This study also demonstrates a framework to assess the communication management strategies of other nations that are encountering global refugee crisis and similar humanitarian relief efforts.